Temporal pairwise spike correlations fully capture single-neuron information - Amadeus Dettner (Nature Portfolio, 2016)
To understand the neural code it is important to determine what spiking features contain the relevant information. Here, the authors use mathematical approaches to show that two pair-wise correlation functions, the autocorrelation function within spike trains and cross-correlation function across stimulus presentations, fully determine the neural information content.